Depthwise microbiome and isotopic profiling of a moderately saline microbial mat in a solar saltern - Paul, Varun (Sci Rep, 2020)
The solar salterns in Tuticorin, India, are man-made, saline to hypersaline systems hosting some uniquely adapted populations of microorganisms and eukaryotic algae that have not been fully characterized. Two visually different microbial mats (termed ‘white’ and ‘green’) developing on the reservoir ponds (53 PSU) were isolated from the salterns. Firstly, archaeal and bacterial diversity in different vertical layers of the mats were analyzed. Culture-independent 16S rRNA gene analysis revealed that both bacteria and archaea were rich in their diversity. The top layers had a higher representation of halophilic archaea Halobacteriaceae, phylum Chloroflexi, and classes Anaerolineae, Delta- and Gamma- Proteobacteria than the deeper sections, indicating that a salinity gradient exists within the mats. Limited presence of Cyanobacteria and detection of algae-associated bacteria, such as Phycisphaerae, Phaeodactylibacter and Oceanicaulis likely implied that eukaryotic algae and other phototrophs could be the primary producers within the mat ecosystem. Secondly, predictive metabolic pathway analysis using the 16S rRNA gene data revealed that in addition to the regulatory microbial functions, methane and nitrogen metabolisms were prevalent. Finally, stable carbon and nitrogen isotopic compositions determined from both mat samples showed that the δ(13)C(org) and δ(15)N(org) values increased slightly with depth, ranging from − 16.42 to − 14.73‰, and 11.17 to 13.55‰, respectively. The isotopic signature along the microbial mat profile followed a pattern that is distinctive to the community composition and net metabolic activities, and comparable to saline mats in other salterns. The results and discussions presented here by merging culture-independent studies, predictive metabolic analyses and isotopic characterization, provide a collective strategy to understand the compositional and functional characteristics of microbial mats in saline environments.